Texto e contexto : implicações no ensino da língua materna - Silva, Claudionor Alves da (2007)
This dissertation about the teaching of Maternal Language offered by the public school and did it leave of the following subject: how the teaching of Maternal Language in the initial years of the fundamental teaching, that take as beginning the use of the text, can it contribute to the students talkative competence in the sense of dominating the oral and written code of the language? This study was accomplished with base in the theoretical-methodological referencial discussed by Kock (2000); (2003a); (2003b); (2003c); (2004a) and (2004b); Travaglia (1997) and (2004) and Marcuschi (2000) and (2004). Thus, it traces a way of the interests by the studies of the language, in the several historical moments, discussing the different language conceptions and its relationship with the teaching of the language. Considering the text as object of teaching of the language, comes, the contribution of the National Curriculares Parameters / Portuguese Language countersigned by the Textual Linguistics that presents an orientation for the analysis of texts. For the accomplishment of the research, it was used documental analysis and of interview done with the teachers of the school research field. The data collected for half of those instruments they showed as significant and valid in the sense of understanding the proposals of teaching of the language in the context of the school. Finally, the analysis of those datums allows to affirm that, in the school, the text is not used indeed about unit of teaching and, consequently, it doesn't objectify the development of the its students' talkative capacity